VDJdb: a curated database of T-cell receptor sequences with known antigen specificity - Shugay, Mikhail; Bagaev, Dmitriy V; Zvyagin, Ivan V; Vroomans, Renske M; Crawford, Jeremy Chase; Dolton, Garry; Komech, Ekaterina A; Sycheva, Anastasiya L; Koneva, Anna E; Egorov, Evgeniy S; Eliseev, Alexey V; Van Dyk, Ewald; et al. (Nucleic acids research, 2018)
The ability to decode antigen specificities encapsulated in the sequences of rearranged T-cell receptor (TCR) genes is critical for our understanding of the adaptive immune system and promises significant advances in the field of translational medicine. Recent developments in high-throughput sequencing methods (immune repertoire sequencing technology, or RepSeq) and single-cell RNA sequencing technology have allowed us to obtain huge numbers of TCR sequences from donor samples and link them to T-cell phenotypes. However, our ability to annotate these TCR sequences still lags behind, owing to the enormous diversity of the TCR repertoire and the scarcity of available data on T-cell specificities. In this paper, we present VDJdb, a database that stores and aggregates the results of published T-cell specificity assays and provides a universal platform that couples antigen specificities with TCR sequences. We demonstrate that VDJdb is a versatile instrument for the annotation of TCR repertoire data, enabling a concatenated view of antigen-specific TCR sequence motifs. VDJdb can be accessed at https://vdjdb.cdr3.net and https://github.com/antigenomics/vdjdb-db.
Keywords: Animals; databáze proteinů; analýza jednotlivých buněk; interakční proteinové domény a motivy; Receptors, Antigen, T-Cell; sekvenční homologie aminokyselin; Protein Interaction Domains and Motifs; vazebná místa; Sequence Homology, Amino Acid; sekvence aminokyselin; High-Throughput Nucleotide Sequencing; vazba proteinů; software; lidé; Antigens; antigeny; hlavní histokompatibilní komplex; Macaca mulatta; Mice; Amino Acid Sequence; Major Histocompatibility Complex; myši; T-lymfocyty; receptory antigenů T-buněk; Models, Molecular; Protein Structure, Secondary; molekulární modely; anotace sekvence; Databases, Protein; vysoce účinné nukleotidové sekvenování; Internet; Sequence Alignment; sekundární struktura proteinů; Molecular Sequence Annotation; Software; T-Lymphocytes; zvířata; Single-Cell Analysis; internet; Protein Binding; sekvenční seřazení; Binding Sites; Humans